C(sp3)–H Bond Functionalization of Alcohols, Ketones, Nitriles, Ethers and Amides using tert-Butyl Hydroperoxide as a Radical Initiator - Wang, Nai-Xing; Zhang, Lei-Yang; Wu, Yue-Hua; Xing, Yalan (Synlett, 2021)
The C(sp3)–H bond is found widely in organic molecules. Recently, the functionalization of C(sp3)–H bonds has developed into a powerful tool for augmenting highly functionalized frameworks in organic synthesis. Based on the results obtained in our group, the present account mainly summarizes recent progress on the functionalization of C(sp3)–H bonds of aliphatic alcohols, ketones, alkyl nitriles, and ethers with styrene or cinnamic acid using tert-butyl hydroperoxide (TBHP) as a radical initiator.1 Introduction2 Oxidative Coupling of Styrenes with C(sp3)–H Bonds3 Decarboxylative Cross-Couplings of α,β-Unsaturated Carboxylic Acids with C(sp3)–H Bonds4 Conclusions
Keywords: C(sp3)–H bond functionalization; radical reactions; styrenes; tert-butyl hydroperoxide; mechanism